Record of Ichthyophis cf. hypocyaneus from the Menoreh mountain range, Central Java with notes on morphology and natural history - Alfonsus Toribio Eko Saputro; Sandra Rafika Devi; Satria Maulana Aziz; Zulqarnain Assidiqi; Adian Dwi Sulistio; Rury Eprilurahman (BRIN Publishing (Penerbit BRIN), 2026)
This is a short communication, so no rigid format is required. Abstract is optional.